2019
DOI: 10.1007/s13224-019-01217-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Pregnancy-Associated Plasma Protein A and Human Chorionic Gonadotropin with Adverse Pregnancy Outcomes: A Prospective Study

Abstract: Purpose This prospective study investigated the relationship between pregnancy-associated plasma protein A (PAPP-A) and human chorionic gonadotropin (hCG) and adverse pregnancy outcomes in the Iranian population. Materials Overall, 994 singleton pregnant mothers of 18-35-year old were referred for first-trimester screening tests, including PAPP-A and β-hCG, at the age of 6 days and 11-13 weeks, and were followed until the end of their pregnancy. The adverse pregnancy outcomes, PAPP-A, and β-hCG serum levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
4
5
0
Order By: Relevance
“…According to our study, while there was a significant difference in PAPP-A and NT measurements between SGA, AGA, and LGA groups, no significant difference was observed between β-hCG levels. Pakniat et al, in their study with 994 pregnant women, found that (in line with our study) low PAPP-A levels were associated with SGA, but β-hCG levels did not show this relationship (33). In the study by Hansen et al from Denmark, 1155 pregnant women were divided into two groups as SGA and AGA.…”
Section: Discussionsupporting
confidence: 88%
“…According to our study, while there was a significant difference in PAPP-A and NT measurements between SGA, AGA, and LGA groups, no significant difference was observed between β-hCG levels. Pakniat et al, in their study with 994 pregnant women, found that (in line with our study) low PAPP-A levels were associated with SGA, but β-hCG levels did not show this relationship (33). In the study by Hansen et al from Denmark, 1155 pregnant women were divided into two groups as SGA and AGA.…”
Section: Discussionsupporting
confidence: 88%
“…We have found studies showing similar results, in which they also observed a greater risk of preeclampsia, preterm labor and low birth weight, in pregnant women with low levels of PAPP-A [8][9][10].…”
Section: Preeclampsiasupporting
confidence: 71%
“…Preeclampsia is detected when the blood pressure exceeds 140/90 mmHg after the 20 th week of pregnancy, along with proteinuria≥300 mg in the 24 hour urine sample or ≥n +1 in the urine dipstick [11].…”
Section: Patientsmentioning
confidence: 99%
“…There are several clinical, biophysical, and biochemical tests to identify women at risk of preeclampsia, but the results of studies reveal that their predictive value is low in the early diagnosis of preeclampsia [10]. One study also showed that low pregnancy-associated plasma protein-A might be used to predict preeclampsia [11].…”
Section: Introductionmentioning
confidence: 99%